The effects of sponges soaked with chlorhexidine gluconate and metronidazole on safety of colonic anastomosis in an experimental model of peritonitis - Aksu, Ali; Bozan, Mehmet Bugra; Kutluer, Nizamettin; Kanat, Burhan Hakan; Ilhan, Yavuz Selim; Turkoglu, Ahmet; Aksoy, Nurullah (Turkish Assoc Trauma Emergency Surgery, 2021)
BACKGROUND: The present study aims to evaluate the use of the chlorhexidine gluconate and metronidazole impregnated compresses concerning anastomosis safety in the left colonic anastomosis in the presence of peritonitis. METHODS: This study was conducted on 21 Wistar-Albino-rats divided into three equal groups. After median laparotomy, the whole layer of the left colon was cut 2 cm over the pelvic peritoneum. The faeces were spread around the injury for fecal contamination. Then, fasia and skin were closed with 3/0 silk. After one day period, relaparatomy was performed. The abdomen was cleared isotonic sodium chloride with impregnated material before starting colonic anastomosis in the first group and then double layer colonic anastomosis was performed. In the second Group-II, abdomen was cleared with the metronidazole impregnated compresses then double layer colonic anastomosis was performed. In the group-III, abdomen was cleared with the chlorhexidine gluconate impregnated compresses then double layer colonic anastomosis was performed. Tissue hydroksiproline levels and anastomosis bursting pressures were measured and histopathologic findings on the anastomosis line were evaluated on the postoperative tenth day by performing relaparatomy. RESULTS: The highest anastomosis bursting pressure was found in Group-III (p<0.05). The highest tissue hydroksiproline level was found in Group-III (p<0.005 Group I-III, Group II-III). When histopathologic findings were evaluated by comparing the three groups in this study, the healing of the intestine tissue score was statistically insignificant between group-II and III, for both group-II and III, healing score was statistically significant higher than Group-I (p<0.05 Group I-III and Group I-II). CONCLUSION: Cleaning the abdomen before the anastomosis using antibacterial soaked material increased resection safety in the presence of peritonitis and anastomosis safety in primary anastomosis.
Peritonitli ortamda klorhexidin glukonat emdirilmiş kompres ve metronidazol emdirilmiş kompres kullanımının bağırsak anastomozu üzerine etkileri
Keywords: Anastomosis leakage; chlorehexidin gluconate; colon anastomosis; peritonitis